2017
DOI: 10.3892/ol.2017.6241
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of mRNAs encoding dihydropyrimidine dehydrogenase and thymidylate synthase are associated with improved survival of patients with hepatocellular carcinoma treated with S-1

Abstract: Abstract. Thymidylate synthase (TYMS) and dihydropyrimidine dehydrogenase (DPYD) are associated with the response of tumors to fluoropyrimidines. The aim of the present study was to investigate the association between the levels of TYMS and DPYD mRNAs and the efficacy of S-1 for treating patients with HCC. A total of 35 patients with HCC who received S-1 upon recurrence (S-1 group) and 20 patients who never received a fluoropyrimidine (control group) were studied. The levels of TYMS and DPYD mRNA in surgically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…However, little is known about TYMS in HCC. Although a previous study suggested that high expression of TYMS may be an independent prognostic factor for HCC, their results are not statistically significant [ 35 ]. In this study, we found that high expression of TYMS was significantly associated with poor OS and PFS using the data extracted from the TCGA-LIHC dataset.…”
Section: Discussionmentioning
confidence: 93%
“…However, little is known about TYMS in HCC. Although a previous study suggested that high expression of TYMS may be an independent prognostic factor for HCC, their results are not statistically significant [ 35 ]. In this study, we found that high expression of TYMS was significantly associated with poor OS and PFS using the data extracted from the TCGA-LIHC dataset.…”
Section: Discussionmentioning
confidence: 93%
“…This is an orally administered preparation that combines tegafur (a prodrug of 5-FU), 5-chloro-2,4-dihydropyridine (a reversible DPD inhibitor), and oteracil potassium (an inhibitor of orotate phosphoribosyltransferase) used to inhibit 5-FU activity within normal gastrointestinal mucosa and hence reduce its toxic side effect on this tissue. Surprisingly, individuals with high expression of DPD showed improved OS after S-1-based chemotherapy [ 26 ]. DPD has been proposed as a therapeutic target for interferon-α (IFN-α) treatment, which is effective in some HCC patients in reducing metastasis by inhibition of epithelial-mesenchymal transition (EMT) through DPD down-regulation.…”
Section: Drug Metabolism (Moc-2)mentioning
confidence: 99%
“…17 The response rate of tumors to fluoropyrimidine drugs depends on thymidylate synthase and dihydropyrimidine dehydrogenase (DPD) activity. 18 DPD is a main enzyme in the biochemical functions of the antimetabolite 5-FU as well as capecitabine. 19-21…”
Section: Introductionmentioning
confidence: 99%